Pelatihan Pembuatan Alat Peraga Difraksi Cahaya berbasis Arduino dan Software Tracker untuk Meningkatkan Kemampuan dan Keterampilan Guru Fisika dalam Mengembangkan Alat Peraga Pembelajaran - Kartini Herlina; Agus Suyatna; I Dewa Putu Nyeneng; Hervin Maulina; B. Anggit Wicaksono (Nuwo Abdimas, 2023)
: Light diffraction material in physics becomes a material that is felt quite difficult for students. Therefore, to reduce these difficulties, teachers are expected to be able to create and develop learning aids that can increase student interest and understanding. This activity aims to improve the ability and skills of physics teachers in making and developing arduino-based light diffraction teaching aids and tracker software. The method used is active participatory. The conclusion of the implementation of this service is that there is an increase in the ability of participants to develop light diffraction displays by utilizing Arduino-based electronic waste and tracker software to train Science Process Skills in the endemic era of covid-19 for high school physics teachers in Lampung Province.